Factors Affecting the Capital Expenditures in Bali Province - Ni Luh Putu Sandrya Dewi; Ni Luh Gede Mahayu Dicriyani (JASF: Journal of Accounting and Strategic Finance, 2018)
Capital Expenditure is budget expenditure used to obtain or add value to assets that benefit more than one accounting period. Infrastructure development in an area is reflected in the allocation of effective capital expenditure from an area. The purpose of this research is to determine the factors that influence capital expenditure in the province of Bali. The object of this study is the report on the realization of the regional expenditure income budget APBD in the District/City in the Province of Bali in the Fiscal Year 2013-2017. The data analysis technique used is multiple linear regression analysis. The results of this study indi cate that regional original income (PAD) has a significant positive effect, balancing funds have no effect and the surplus financing budget (SILPA) effect on capital expenditure negatively in the province of Bali.